SeminarRole of Universities in R&D - Ratnam, K. J. (1987)
The paper not pose the question of whether universities have a role to play in R&D, taking it to be axiomatic that they do in present day circumstances. There is however a need to examine what this role ought to be, how it can be shaped by varying external.